2003
DOI: 10.1259/bjr/69317841
|View full text |Cite
|
Sign up to set email alerts
|

High resolution MRI of the brain at 4.7 Tesla using fast spin echo imaging

Abstract: Over recent years, high field MR scanners (3 T and above) have become increasingly widespread due to potential advantages such as higher signal-to-noise ratio. However, few examples of high resolution images covering the whole brain in reasonable acquisition times have been published to date and none have used fast spin echo (FSE), a sequence commonly employed for the acquisition of T(2) weighted images at 1.5 T. This is mostly due to the increased technical challenges associated with uniform signal generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…1 The resulting T 2 weighted images confirmed the clinical diagnosis of subgaleal haemorrhage. In addition to uncal and transtentorial herniation, haemorrhagic infarction involving deep grey matter, cerebellum, and spinal cord were observed (fig 1).…”
supporting
confidence: 59%
“…1 The resulting T 2 weighted images confirmed the clinical diagnosis of subgaleal haemorrhage. In addition to uncal and transtentorial herniation, haemorrhagic infarction involving deep grey matter, cerebellum, and spinal cord were observed (fig 1).…”
supporting
confidence: 59%
“…MRI studies at 3 T demonstrated substantial increase of 1/T 0 2 in the SN of PD patients but not 1/T 2 , 16 as predicted. In subsequent studies, the results were confirmed and also extended to the basal ganglia, 17,18 clearly indicating that 1/T 0 2 yields stronger correlations with brain iron in PD than 1/T 2 . In principle, iron content could also be investigated using 1/T Ã 2 (those signal changes caused by the sum of 1/T 0 2 and 1/ T 2 ).…”
Section: Imaging Of Brain Ironmentioning
confidence: 61%
“…3-T clinical systems are now commercially available and 7-T and 8-T human research systems are in use (6,7). Early reports demonstrate the utility of modern high field systems in detecting different types of brain lesions (8 -10) and in demonstrating underlying anatomy with high spatial resolution (11,12). Early measurements on high field systems have shown increased SNR and CNR and also increased artifact conspicuity (12).…”
mentioning
confidence: 99%